The renaissance New Testament ; v. 4 - Yeager, Randolph O. (Bowling Green, KE Renaissance, 1979)
Contents : v. 3 : Harmonistic syllabus of the Gospels based on the Gospel of Mark
Keywords: Bible. N.T. -- criticism, interpretation, etc